Sensory properties of the PII signalling protein family. (23rd November 2015) - Forchhammer, Karl; Lüddecke, Jan
Abstract : PII signalling proteins constitute one of the largest families of signalling proteins in nature. An even larger superfamily of trimeric sensory proteins with the same architectural principle as PII proteins appears in protein structure databases. Large surface‐exposed flexible loops protrude from the intersubunit faces, where effector molecules are bound that tune the conformation of the loops. Via this mechanism, PII proteins control target proteins in response to cellular ATP/ADP levels and the 2‐oxoglutarate status, thereby coordinating the cellular carbon/nitrogen balance. The antagonistic (ATP versus ADP) and synergistic (2‐oxoglutarate and ATP) mode of effector molecule binding is further affected by PII ‐receptor interaction, leading to a highly sophisticated signalling network organized by PII . Altogether, it appears that PII is a multitasking information processor that, depending on its interaction environment, differentially transmits information on the energy status and the cellular 2‐oxoglutarate level. In addition to the basic mode of PII function, several bacterial PII proteins may transmit a signal of the cellular glutamine status via covalent modification. Remarkably, during the evolution of plant chloroplasts, glutamine signalling by PII proteins was re‐established by acquisition of a short sequence extension at the C‐terminus. This plant‐specific C‐terminus makes the interaction of plant PII proteins with one of its targets, the arginine biosynthetic enzyme N ‐acetyl‐glutamate kinase, glutamine‐dependent. Abstract : PII signaling proteins function as multitasking signal integrators to control cellular activities in response to the metabolite status. PII proteins bind adenylnucleotides, and when ATP is bound, they may interact with 2‐oxoglutarate (2‐OG). Glutamine signalling occurs either by post‐translational modification through glutamine‐dependent modifying enzymes, as the case in various bacteria, or by direct interaction on an additional C‐terminal subdomain, as in plants.